Analgesic Effectiveness of ant Nest Ethanol Extract (Myrmecodia Pendens) on white Mice (Mus Musculus) - Maulana, Fajar; Lukman Hardia; Angga Bayu Budiyanto (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Pain is an unpleasant sensation emotionally and subjectively, indicating damaged tissue such as inflammation or a more significant condition. Myalgia, or often known as muscle pain. In Indonesia, the percentage of Myalgia sufferers is around 45-59%. This study applies an experimental method with a pretest-posttest group design. In this study, 25 mice were used which were divided into 5 groups, namely negative control (Na CMC 1%), positive control (mefenamic acid) and 3 groups given a dose of ant nest extract (17.5 mg/kgBW, 35 mg/ kgBW, 70 mg/kgBW). The analgesic effectiveness test used was the hot plate method with the writhing response parameter measured for 3 hours with a measurement interval of every 30 minutes. The results showed that the ethanol extract of ant nests showed positive tannin, alkaloid and flavonoid compounds. Data analysis on the comparison of dose groups showed that the doses of 17.5 mg and 35 mg had a significant value of <0.05 with a dose of 70 mg, in the positive control group had a significant value of >0.05 compared to the 70 mg ant nest extract dose group, which means there is no significant difference between the two. On the contrary, the negative control group showed a significant value of <0.05 compared to all treatment groups, which indicates a significant difference. The conclusion of this study is that the dose of ethanol extract of ant nest 70 mg has good analgesic effectiveness, approaching the effectiveness of the positive control of mefenamic acid.